2009
DOI: 10.1016/j.proci.2008.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Shock-tube study of the ignition of methane/ethane/hydrogen mixtures with hydrogen contents from 0% to 100% at different pressures

Abstract: The ignition delay times of diluted hydrogen / reference gas (92% methane, 8% ethane) / O 2 / Ar mixtures with hydrogen contents of 0, 40, 80 and 100% were determined in a highpressure shock tube at equivalence ratios  = 0.5 and 1.0 (dilution 1:5). The temperature range was 900 K  T  1800 K at pressures of about 1, 4 and 16 bar.The reference gas and the 40% hydrogen / 60% reference gas data showed typical characteristics of hydrocarbon systems and can be represented by:(reference gas) andThe pure hydrogen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
88
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 20 publications
8
88
1
Order By: Relevance
“…In this study, the ignition delay time was defined as the interval between the arrival of the reflected shock wave and the initiation of the main ignition, that is, the maximum HO· emission. The ignition delay times obtained in this manner agreed with the calculated values presented in [14]. A comparison among the experimental and calculated (GRI-Mech 3.0 [17]) ignition delay times from this study and those of Petersen et al [18], Wang et al [19] and Hughes et al [20] is shown in Figure 3.…”
Section: Results and Data Analysissupporting
confidence: 86%
See 3 more Smart Citations
“…In this study, the ignition delay time was defined as the interval between the arrival of the reflected shock wave and the initiation of the main ignition, that is, the maximum HO· emission. The ignition delay times obtained in this manner agreed with the calculated values presented in [14]. A comparison among the experimental and calculated (GRI-Mech 3.0 [17]) ignition delay times from this study and those of Petersen et al [18], Wang et al [19] and Hughes et al [20] is shown in Figure 3.…”
Section: Results and Data Analysissupporting
confidence: 86%
“…The predicted values from these mechanisms agree well with the experimental values for pure methane. For the ignition delay times of methane, the experimental results from the present study are about 4.5 times longer than those obtained by Herzler et al using 92% methane and 8% ethane [14]. However, addition of ethane reduces the ignition delay time of methane.…”
Section: Results and Data Analysiscontrasting
confidence: 71%
See 2 more Smart Citations
“…More recently, Petersen et al (2007) used the reflected shock technique to measure ignition delay times from methane/hydrogen/air mixtures under lean burn ( = 0.5) combustion conditions over a range of pressures near 21 atm (18.2-25.1 atm) and temperatures ranging from 1141 K to 1553 K. In agreement with the earlier work of Cheng and Oppenheim, the effect of hydrogen addition on ignition delay was found to increase with increasing amounts of hydrogen in the blend-20% H 2 addition decreased the ignition delay by a factor of 3 while the addition of 40% H 2 resulted in a nearly 10 fold decrease in ignition delay compared to the base methane fuel. Similarly, Herzler and Naumann (2009) Huang et al (2006) that the effect of hydrogen in promoting ignition increases with temperature and decreases with pressure. Other fundamental premixed combustion studies have indicated that the preferential diffusion of hydrogen in a turbulent combustion event results in a higher flame propagation rate, even when the laminar flame speed is constant (Kido et al 2002).…”
Section: Previous Studies Of Hydrogen-enriched Methane Combustionmentioning
confidence: 99%